Silver nanoparticles in silicate glass prepared by UV laser irradiation: dependences of size and atomic structure of particles upon irradiation parameters. (May 2016) - Dubiel, M; Heinz, M; Srabionyan, V V; Pryadchenko, V V; Avakyan, L A; Zubavichus, Ya V; Meinertz, J; Ihlemann, J; Bugaev, L A
Abstract: Plasmonic Ag nanostructures were generated in glass surfaces by means of UV laser irradiation (193 nm). The aim of the work was to identify the correlations between the atomic structure of such nanoparticles and their optical properties. The structural characterization of the samples, prepared with different number of laser pulses was performed by Ag K -edge EXAFS. The processing of the spectra by the Fourier-transform analysis gave the values of Ag-Ag and Ag-O interactions averaged over ionic and neutral states of silver in the sample. The consistent analysis of the behavior of features in optical spectra and the obtained dependencies of Ag-Ag and Ag-O structural parameters upon the number of laser pulses enabled to suggest the mechanism of plasmonic Ag nanoparticles formation in silicate glass, which is influenced by the interaction with polyvalent ions (for example Fe 2+ ) and by defect centers (for example HTC and NBOHC centers) generated by UV irradiation.